Pengaruh Store Image, Store Atmospherics, Store Theatrics, dan Social Factors Terhadap Pembelian Tidak Terencana (Studi Kasus Pada Luwes Pasar Swalayan Ungaran) - Aditya Yudatama; Saryadi Saryadi; Hari Susanto Nugroho (Universitas Diponegoro, 2012)
The purpose of this study is to find out the influence of store image, store atmospherics, store theatrics and social factors on impulse buying. Type of research that we used here is explanatory research which explains the relations among the variables of the study. The number of the sample was 92 people. Sampling technique using purposive sampling. Data collection technique using questionnaires directly to the 92 respondents Luwes visitors who have made an impulse buying. Test the questionnaire using a cross table analysis, validity test, reliability test , simple linear regression, multiple linear test, and statistical tests using t test and F test. From the result of the analysis revealed that the store image has positive and significant impact on impulse buying indicated by the coefficient correlation of 0.870 and the coefficient regression of 0.452. Store atmospherics have a positive and significant impact on impulse buying is indicated by the coefficient correlation of 0.887 and the coefficient regression of 0.364. Store theatrics have a positive and significant impact on impulse buying is indicated by the correlation coefficient of 0.476 and the regression coefficient of 0.382. Social factors have a positive and significant impact on impulse buying is indicated by the coefficient correlation of 0.668 and the coefficient regression of 0.580. While simultaneously, store image, store atmospherics, store theatrics and social factors have a positive and significant impact on impulse buying as indicated by the linear regression test of 0.177 to store images, store atmospherics of 0.184, 0.095 for store theatrics, and social factors for 0.114. Based on the results of the research studies, advice that can be given to the company store is to create a better environment to enlarge the opportunities for the creation of impulse buying in supermarket Luwes Ungaran thus increasing the overall sales volume.